Lexical Cohesion and Field of News Stories Text of The Jakarta Post - Rahmat Fajri; Amrin Saragih (LINGUISTIK TERAPAN, 2016)
This study investigates lexical cohesion and field in news stories text of the Jakarta Post. The objectives of the study are (1) to determine the patterns of lexical cohesion used in Jakarta Post in fields of politics, economics, and culture, (2) to describe the realizations of lexical cohesion, and (3) to explain the reasons. The study is based on descriptive qualitative design through documentary technique. The sources of data were taken from 12 news stories text which published on April 2015. The data were analyzed by using interactive technique Miles and Huberman. This research results are as follows firstly, the patterns of lexical cohesion were used in news stories text in fields of politics, economics, and culture. In politics text, the existence of repetition, synonymy, antonymy, and hyponymy. In economics text, the existence of repetition, hyphonymy, and meronymy. In culture text, the existence of repetition, synonymy, antonymy, hyponymy, and meronymy. Secondly, the realizations of lexical cohesion in news stories text of the Jakarta Post were (1) repetition, (2) synonymy, (3) antonymy, (4) hyponymy, and (5) of meronymy. Thirdly, the reasons of lexical cohesion used in news stories text of the Jakarta Post, (1) repetition to keep one or more lexical string relative simple, while complex lexical relations are constructed around them (2) synonymy  to avoid the repetition, and it may also differ in attitude (3) antonymy to construct classifying taxonomies in which one class of phenomenon is distinguished from another (4) hyponymy to develop elaboration with each other, and (5) meronymy to extend domain with each other. Keywords: cohesion, field, Jakarta Post, lexical, news story